Dengue Virus Type 2 in Travelers Returning to Japan from Sri Lanka, 2017 - Motoyuki Tsuboi (Emerging Infectious Diseases, 2017)
In June 2017, dengue virus type 2 infection was diagnosed in 2 travelers returned to Japan from Sri Lanka, where the country’s largest dengue fever outbreak is ongoing. Travelers, especially those previously affected by dengue fever, should take measures to avoid mosquito bites.